Promoted crystallization of silicoaluminophosphate zeolites: an efficient way to accelerate crystallization rate and increase solid yield. Issue 13 (24th March 2021) - Yuan, Delin; Wang, Qianjin; Shang, Yunshan; Liu, Hua; Xing, Aihua
Abstract : SAPO-34 with 100% yield has been synthesized by an acid-assisted method, which is also applicable to the synthesis of other silicoaluminophosphate zeolites. Abstract : Ultra-high yield of a silicoaluminophosphate zeolite is reported with a facile and cost-effective acid-assisted method. The lower gel pH due to the addition of an acid enhances the activity of the phosphorus species and promotes the polymerization of the aluminophosphate precursors, which accelerates the crystallization rate and increases the yield.